The Impact of Domestic Tourist Spending on the Economy of West Sumatra Province - Arsenal Priadi; Elvina Primayesa (SAFE-Network, 2026)
This study analyzes the impact of domestic tourist expenditure on the economy of West Sumatra Province using the Input-Output approach. The scope of the study is focused on sectors related to tourism activities, particularly intersectoral linkages and the formation of regional economic output. The objective of this study is to examine the development of domestic tourist expenditure, the patterns of forward and backward linkages among tourism-related sectors, and their contribution to the regional economy. This study uses secondary data from BPS, the Ministry of Tourism, and other related sources, with Leontief Input-Output analysis updated through the RAS method. The results show that the increase in the number of domestic tourist visits is not always followed by an increase in expenditure, so the resulting economic impact is not always optimal. Transportation, trade, accommodation, and food and beverage sectors play an important role in spreading multiplier effects to other sectors. Domestic tourist expenditure has strong potential to stimulate West Sumatra’s economic output, but its effectiveness is highly determined by the structure of intersectoral linkages and the level of tourist spending.